Looking for the proletariat : Socialisme ou Barbarie and the problem of worker writing - Hastings-King, Stephen William (Historical materialism book series ;, 2014)
Looking for the Proletariat is the first English-language history of the French revolutionary group Socialisme ou Barbarie from 1949 to 1957. It explores the group, its contexts and the collapse of the Marxist Imaginary captured in texts by Daniel Mothé.